Integrating biocatalysis and multicomponent reactions. (November 2018) - Lambruschini, Chiara; Basso, Andrea; Banfi, Luca
Graphical abstract: Abstract : While often multicomponent reactions (MCR) are used for the diversity-oriented synthesis of racemic (or achiral) molecular entities, this short review describes two alternative approaches for accessing enantiopure products exploiting the power of biocatalysis. Enzymes or microorganisms may be used for preparing enantiopure MCR inputs or for resolving racemic (or achiral) MCR adducts.